2011
DOI: 10.1590/s0102-311x2011000500020
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of salivary gland tumors: an assessment of 303 patients

Abstract: Salivary gland neoplasms are remarkable for their histological diversity and several studies point to their varied occurrence in the population. Clinical aspects were histologically assessed to determine possible associations and define parameters to differentiate benign and malignant neoplasms. The case files of patients diagnosed with epithelial salivary gland tumors between 1989 and 2005 were reviewed. A majority (71%) of the 303 salivary gland tumors studied were benign and pleomorphic adenoma were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
1
10
2
2
Order By: Relevance
“…The present study's evaluation of 184S GT cases indicates that the majority of tumors were malignant, in contrast to the results of most studies in west and south Iran and other countries (1,4,6,(10)(11)(12)(13) and in agreement with a few studies (14,15).…”
Section: Discussionsupporting
confidence: 83%
“…The present study's evaluation of 184S GT cases indicates that the majority of tumors were malignant, in contrast to the results of most studies in west and south Iran and other countries (1,4,6,(10)(11)(12)(13) and in agreement with a few studies (14,15).…”
Section: Discussionsupporting
confidence: 83%
“…Salivary gland neoplasms are remarkable for their histological diversity and pose a particular challenge to the pathologist because of their complex classification and the rarity of several varieties [1,2]. Most publications in the literature on major and minor salivary gland tumours, find it difficult to evaluate the real frequency and site distribution of salivary gland tumours [2,3]. They are relatively rare, accounting for approximately 2% to 10% of all head and neck tumours [4] worldwide and are more commonly found in the parotid gland.…”
Section: Introductionmentioning
confidence: 99%
“…Even though Middle East and America presented overall higher prevalence rates than other locations, such as the Europe and Asia, little variation and high imprecision were observed. It is well established that differences in the prevalence of diseases are usually found even within the same country due to epidemiological factors such as genetics, exposition to radiation, viral infection, or consumption of tobacco and alcohol 3,6 . Therefore, not only variability across macro‐geographical regions should be considered, but also differences across micro‐geographical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Mucoepidermoid carcinoma (MEC) is one of the most frequent malignancies of the salivary glands. Studies have shown that MEC may represent up to 45% of all MiSGT 5,6 . Histologically, MEC usually presents two distinct patterns: (a) cystic structures lined by mucin‐producing, intermediate, or epidermoid cells; or (b) solid cellular proliferation of intermediate and epidermoid cells associated with high rates of atypia, anaplasia, and mitoses 7 .…”
Section: Introductionmentioning
confidence: 99%